1994
DOI: 10.1002/bjs.1800810128
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the duodenum: Factors influencing survival

Abstract: The records of 66 patients with histologically proven adenocarcinoma of the duodenum were reviewed retrospectively to determine factors influencing survival. The parameters studied were age, sex, weight loss, jaundice, anaemia, duodenal stenosis, type of surgical procedure, tumour size and location, depth of parietal invasion, presence and location of lymph node metastases, and pancreatic invasion. These factors were assessed in a group of 46 patients who underwent curative resection of the tumour; 20 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
47
3
8

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 15 publications
5
47
3
8
Order By: Relevance
“…Only one patient experienced a treatment-related deterioration in PS, other patients maintained a PS of 2. Although the series is small, the results in terms of overall survival, symptomatic responses, the improvement or maintenance of a good PS as an indicator of quality of life and the generally low toxicity of therapy, suggests that there may be benefit of 5FU-based chemotherapy compared with palliative surgery alone (Sakker and Ware, 1973;Rotman et al, 1994). Various series or case reports have suggested that small bowel adenocarcinoma is a chemo-or radiosensitive disease, particularly in comparison with pancreatic cancer (Sakker and Ware, 1973;Jigyasu et al, 1984;Okhusa et al, 1991;Yeung et al, 1993;Coia et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Only one patient experienced a treatment-related deterioration in PS, other patients maintained a PS of 2. Although the series is small, the results in terms of overall survival, symptomatic responses, the improvement or maintenance of a good PS as an indicator of quality of life and the generally low toxicity of therapy, suggests that there may be benefit of 5FU-based chemotherapy compared with palliative surgery alone (Sakker and Ware, 1973;Rotman et al, 1994). Various series or case reports have suggested that small bowel adenocarcinoma is a chemo-or radiosensitive disease, particularly in comparison with pancreatic cancer (Sakker and Ware, 1973;Jigyasu et al, 1984;Okhusa et al, 1991;Yeung et al, 1993;Coia et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Nenhum de nossos pacientes apresentou icterícia, que é relatada em até 54% dos enfermos 16,19,20 . Apenas a portadora de adenocarcinoma viloso da segunda porção teve surtos de pancreatite aguda, sem icterícia.…”
Section: Discussionunclassified
“…A GDPC, não obstante seu vulto, é o melhor tratamento para as neoplasias da segunda porção duodenal, opinião que é corroborada pela maioria dos autores 2,7,17,19,20,21 . Mesmo a presença de metástases linfonodais parece não ter impacto na sobrevida dos enfermos e não deve contra-indicar a ressecção 2,23 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The 5 year survival rate varies widely according to different series published, but is generally reported to be >40% in case of curative resection 5 . The presence of lymph node metastases is not a bad prognostic factor in most series and is not a contraindication for curative resection 6 .…”
mentioning
confidence: 99%